MASS TRANSFER BlOT NUMBERS - Parti, Mihály (Periodica Polytechnica Mechanical Engineering, 1994)
The heat transfer Biot number has a key role in studying transient heat transfer. In prin-ciple an analogous mass transfer Biot number can be derived for transient mass transfer. Substituting that mass transfer Biot number for the heat transfer Biot number all the re-sults and statements of transient heat transfer are valid for transient mass transfer. In our experience the mass transfer Biot number used in the relevant literature for that aim does not give similarity between the two transfer processes. Using a simple model it was shown that three mass transfer Biot numbers can be derived: the fluid-phase, the solid-phase and the analogous mass transfer Biot number. In the relevant literature the fluid-phase mass transfer Biot number is predominantly used which does not give similarity between the two processes. The solid-phase mass transfer Biot number gives a limited similarity of the two processes because of the limited boundary condition used at the interface. The mass transfer Biot number based on the equilibrium conception at the interface gives a general similarity. This assumes only equilibrium at the interface for both processes, consequently it handles the two transfer processes on the same basis.